2 D Materials for Inhibiting the Shuttle Effect in Advanced Lithium–Sulfur Batteries. Issue 6 (18th November 2019) - Ali, Tariq; Yan, Chenglin
Abstract: A lithium–sulfur battery is a new energy storage device with low cost, high energy storage density, and environmental protection. It is an important tool for future battery systems. However, owing to the shuttle of polysulfides, insulation performance of sulfur, and volume change, capacity decay and cycle instability result, which limits the future application of lithium–sulfur batteries. 2 D materials, such as graphene, carbide, nitride, sulfide, oxide, and their aggregates, provide high surface area to improve sulfur utilization and cycle performance. In this Minireview, various 2 D materials are summarized that use physical confinement and chemical interactions to inhibit the shuttle of polysulfides. We outline the controlled spacing of 2 D materials, abundant active sites, and large transverse size separators and interlayers. The effects on the interlayer and separator based on 2 D materials at the lithium anode prevent polysulfide dissolution are also reviewed. Finally, the challenges and prospects of 2 D materials for lithium–sulfur batteries are discussed. Abstract : Shuttle stop : Shuttle‐effect inhibition owing to the incorporation of various 2 D materials like graphene, modified graphene, carbides, nitrides, and sulfides in the cathode, separator/interlayer, and anode are presented in this Minireview.